2014
DOI: 10.1002/jsfa.6694
|View full text |Cite
|
Sign up to set email alerts
|

Influence of closure, phenolic levels and microoxygenation on Cabernet Sauvignon wine composition after 5 years' bottle storage

Abstract: Closure OTR strongly affects sulfur dioxide levels - the primary antioxidant in wine - in aged wine, but phenolic levels substantially alter the secondary reactions of oxidative aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
2
19
0
2
Order By: Relevance
“…PvPP is a synthetic polymer that complexes with wine phenolic compounds by hydrogen bonds. Han et al (2015) demonstrated that wines made from Cabernet Sauvignon cultivar treated with PvPP showed significant losses in polyphenol concentration as PvPP binds and removes phenolics. In addition to PvPP, casein fining can promote a decrease in polyphenol in monomeric and oligomeric flavanols as well as proanthocyanidins as shown by Braga, Cosme, Ricardo-da-Silva, and Laureano (2007).…”
Section: Total Polyphenols and Total Anthocyanins And Total Tanninsmentioning
confidence: 99%
“…PvPP is a synthetic polymer that complexes with wine phenolic compounds by hydrogen bonds. Han et al (2015) demonstrated that wines made from Cabernet Sauvignon cultivar treated with PvPP showed significant losses in polyphenol concentration as PvPP binds and removes phenolics. In addition to PvPP, casein fining can promote a decrease in polyphenol in monomeric and oligomeric flavanols as well as proanthocyanidins as shown by Braga, Cosme, Ricardo-da-Silva, and Laureano (2007).…”
Section: Total Polyphenols and Total Anthocyanins And Total Tanninsmentioning
confidence: 99%
“…Wine astringency also decreases because of a decline in the mean polymerization degree of tannins [10], while the hue and color stability usually increase due to the formation of stable orange-yellow pigments such as pyranoanthocyanins [11]. So far, most research observing wine flavor changes during bottle aging has focused on dry red wines [1,12], or is only concerned about the flavor quality, determined either by volatile compounds or non-volatile compounds [3,4,13,14]; comprehensive investigations monitoring the evolution of rosé and dry white wines’ flavor profiles and oxidation patterns during bottle aging are quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Under ideal experimental conditions, the O 2 :SO 2 molar ratio of the reaction is 1:2 [33], corresponding to a maximum theoretical consumption of 4 mg of SO 2 per mg of consumed O 2 . During storage of wine in bottle, a mass ratio below 4 or a molar ratio of 1 :< 2 means that a part of the oxygen which enters inside the bottle does not indirectly reacts with SO 2 , but reacts with other constituents of wine [33,34]. Nucleophilic compounds come into competition with sulfites to react with the quinones.…”
Section: Sulfite Versus Oxygen Consumptionmentioning
confidence: 99%